2012
DOI: 10.1097/igc.0b013e31823b3650
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Body Mass Index and Prevalence of Hereditary Nonpolyposis Colorectal Cancer in Korean Patients With Endometrial Cancer

Abstract: Body mass index was not different between sporadic endometrial cancer and HNPCC-related endometrial cancer in Koreans. However, BMI proportions in the patients with HNPCC related to endometrial cancer was significantly different from those in sporadic endometrial cancer. Specifically, among nonobese patients, the proportion of normal weight was significantly high in Korean women with HNPCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(21 reference statements)
2
3
0
Order By: Relevance
“…Consistently with previous studies (14,16), no differences in the prevalence of DM or other chronic illnesses between the study groups were identified in the current study. With regard to BMI and other co-morbidities, the similarities between LS and sporadic EC patient cohorts may imply that sporadic and hereditary EC patients share a common risk factor profile.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Consistently with previous studies (14,16), no differences in the prevalence of DM or other chronic illnesses between the study groups were identified in the current study. With regard to BMI and other co-morbidities, the similarities between LS and sporadic EC patient cohorts may imply that sporadic and hereditary EC patients share a common risk factor profile.…”
Section: Discussionsupporting
confidence: 80%
“…These studies have suggested that EC women with a family history of CRC or suspected LS appear to be obese less often compared with EC women with no CRC family history (14)(15)(16)(17)(18). However, Lynch mutation carriers with EC have also been reported to be more obese compared with women with sporadic EC (16), whereas others (13) have reported no significant difference in BMI between these two patient groups, which is in line with the results presented in the current study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We have previously compared the BMI between the sporadic and hereditary nonpolyposis colorectal cancer (HNPCC)-related endometrial cancer groups and found that there was a difference in the proportion. Especially, among the nonobese patients, the proportion of normal weight was significantly higher in the HNPCC-related group than in the sporadic endometrial cancer group [20]. In this study, no significant difference was identified in BMI and diabetes between the hereditary group (according to the presence of synchronous malignancy) and the sporadic group.…”
Section: Discussionmentioning
confidence: 81%
“…The doctors in our country were probably not aware of familial cancer risk as in Western countries, while the patients might be uncertain about their relatives' detailed health conditions or history. We were aware of a few studies from Asia that described HNPCC-related EC in Koreans [ 16 33 34 ]. Findings from their studies and our study might raise awareness of this topic in Thai and other Asian populations.…”
Section: Discussionmentioning
confidence: 99%